The concept and current state of legal regulation on staffing of the State Criminal Executive Service of Ukraine - K. Yu. Sverdlin (Bulletin of Kharkiv National University of Internal Affairs)
Ukraine has been reforming the penitentiary system for several years in order to humanise and bring it in line with European standards, and even today, in the face of a full-scale Russian military invasion, the processes of transformation and improvement of this system in our country have not stopped, as evidenced by the emergence of an updated strategic course for further changes and development of the national penitentiary system. Over the past few years, important positive results have already been achieved on this path, but a number of problems remain unresolved, slowing down the reform process and the achievement of its goals.